(untitled) - Franquiz, Bob; (1973-...) (U.S.A., 2013)
When someone becomes a new Christian, they are often left wondering what to do next. What does it mean to be a Christian' Where do they start' Bob Franquiz, founding pastor of Calvary Fellowship in Miami has built a road map for new Christians in Begin? He leads young believers to the starting points--Bible reading, prayer, church, fellowship, and baptism--that lead to a rich life of following Christ. New Christians will discover the practices that encourage spiritual growth and develop a process that allows them to keep growing closer to God for a lifetime.
Keywords: Religion (discipline)